Morphological and Anatomical Variations among the Genera of Gleicheniaceae - Chin, Lea Yen (2006)
A research of morphological and anatomical variation among the genera of Gleicheniaceae in Peninsular Malaysia was carried out from June 2003 to May 2005. Eighteen species of Gleicheniaceae (including 9 varieties) from 4 genera namely 9 species of Dicranopteris, 3 species of Diplopterygium, 3 species of Gleichenia and 3 species of Sticherus had been examined. These ferns were collected from the fringes of the Lowland Dipterocarp Forest (LDF), Hill Dipterocarp Forest (HDF), Lower Montane Forest (LMF) and Upper Montane Forest (UMF). All species of Gleicheniaceae are sun-ferns that grow well on poor clay soils or nutrient poor soil with small demand of mineral substances. They make adaptation by their creeping rhizomes and by the indefinite growth of the fronds that form thickets. Morphological studies including frond architecture and study of stipe anatomy were conducted, as they are taxonomically significant for delimiting genera and species within Gleicheniaceae. Six types of frond architecture (including the modification from the basic) were observed in this study with each corresponding to a distinct genus and also to certain species. Furthermore, the characters of the dermal appendages (hairs and scales) at the stipe, costae and costules of the lamina segments are found to be significant for delimiting of species in the genera. The presence of additional branches and the shape of pseudostipules, size, texture, the condition of the upper or lower surface of the lamina segments and venation pattern were the basis for the classification of genera and some species. The stipe anatomy revealed that Gleicheniaceae has three types of vascular bundle in the stele. The C–shaped form was found in genera Dicranopteris (excluding D. linearis var. linearis), Diplopterygium and Sticherus; circular-shaped vascular bundle was found in genus Gleichenia whereas D–shaped vascular bundle was found in only one species of Dicranopteris, namely the D. linearis var. linearis. The features such as the distribution of endodermis, different width of the adaxial gap, different forms of the adaxial hooks and different amount and distribution of xylem and protoxylem groups are important for identification. Variation in the vascular bundle of Gleicheniaceae was found to be taxonomically significant at the genus and species levels.